Pemilihan Aplikasi E-Commerce untuk Pengembangan Bisnis Virtual Menggunakan Metode VIKOR dan Rank Sum - Permata Permata (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
Choosing an e-commerce application is an important process for businesses to ensure that the chosen platform can optimally support their operational needs and marketing strategies. Choosing the right e-commerce app will help businesses improve operational efficiency, expand market reach, and increase customer satisfaction, all of which contribute to long-term success. The main issues in the selection of e-commerce applications are often related to the suitability of features, cost, and system integration. The combination of the VIKOR and Rank Sum methods in MCDM can provide a more objective and comprehensive solution. The Rank Sum method is used to give weight to each criterion based on the existing ranking, while VIKOR helps to select the best alternative based on the evaluation of compromises between alternatives. This combination approach provides an advantage in dealing with problems involving many alternatives and complex criteria, with more detailed and fair solutions. The ranking results using the VIKOR method show that the E-Commerce Application 2 is the best alternative with a VIKOR index value of 0, which means that this application is the closest to the ideal solution and has the best performance in meeting the predetermined criteria. In second place, there is the E-Commerce Application 1 with a VIKOR index value of 0.69, which shows that although it is not as optimal as the E-Commerce 2 Application, this application is still an excellent choice based on the evaluation criteria. The E-Commerce 4 app came in third with a score of 0.934, slightly worse compared to the previous app, but still in the acceptable category.